Short progression-free survival predicts for poor overall survival in older patients with multiple myeloma treated upfront with novel agent-based therapy - Migkou, M.; Kastritis, E.; Roussou, M.; Gkotzamanidou, M.; Gavriatopoulou, M.; Nikitas, N.; Mparmparoussi, D.; Matsouka, C.; Gika, D.; Terpos, E.; Dimopoulos, M.A. (European Journal of Haematology, 2011)
To assess the importance of the quality of response and of early relapse in unselected elderly patients with myeloma treated upfront with novel agents. Methods: We analyzed 135 unselected transplant-ineligible patients older than 65yr who were treated upfront with novel agent-based regimens in a single center. Results: On intent to treat, 81% of patients achieved a response (28% sCR/CR, 23% VGPR, and 30% PR). Median progression-free survival (PFS) for patients who achieved sCR/CR was 31 vs. 20months for VGPR and 23months for PR (P=0.048). Median overall survival (OS) for patients with sCR/CR was 62months, 53months for VGPR and 38months for patients with PR (P=0.028). Early relapse (PFS<12months) was more common in patients with PR (39% vs. 21% for VGPR vs. 3% for sCR/CR). Patients who relapsed or progressed <12months from initiation of treatment had a median OS of 15.4months compared with 53months (P<0.001) for patients who had a PFS>12months despite the fact that after relapse or progression most patients were treated again with novel agents. In multivariate analysis, short PFS was the most significant adverse prognostic factor affecting OS, associated with a 7.25-fold (P<0.0001) increase in the risk of death. Conclusion: In newly diagnosed patients over 65yr, treated upfront with novel agents achievement of CR and a PFS ≥12months is associated with improved outcome. Patients who fail to respond or experience early relapse after primary therapy with novel agent-based regimens should be encouraged to participate in clinical trials of novel agents and combinations. © 2011 John Wiley & Sons A/S.
Keywords: bortezomib; Lenalidomide; Prognosis; Thalidomide